Device-Related Thrombus After Left Atrial Appendage Closure: Incidence, Predictors, and Outcomes - Dukkipati, Srinivas R.; Kar, Saibal; Holmes, David R.; Doshi, Shephal K.; Swarup, Vijendra; Gibson, Douglas N.; Maini, Brijeshwar; Gordon, Nicole T.; Main, Michael L.; Reddy, Vivek Y. (Circulation (New York, N.Y.), 2018)
BACKGROUND:In patients with atrial fibrillation, left atrial appendage closure with the Watchman device prevents thromboembolism from the left atrial appendage; however, thrombus may form on the left atrial face of the device, and then potentially embolize. Herein, we studied the incidence, predictors, and clinical outcome of device-related thrombus (DRT) using a large series of clinical trial cohorts of patients undergoing Watchman implantation. METHODS:We studied the device arms of 4 prospective Food and Drug Administration trialsPROTECT-AF (Watchman Left Atrial Appendage System for Embolic Protection in Patients With Atrial Fibrillation) (n=463); PREVAIL (Evaluation of the Watchman LAA Closure Device in Patients With Atrial Fibrillation Versus Long Term Warfarin Therapy) (n=269); CAP (Continued Access to PROTECT AF registry) (n=566); and CAP2 (Continued Access to PREVAIL registry) (n=578). Surveillance transesophageal echocardiographs were performed at 45 days and 12 months in all patients, and also at 6 months in the randomized control trials. We assessed both the incidence of DRT during these transesophageal echocardiographs (and other unscheduled transesophageal echocardiographs), and clinical outcomes of postprocedure stroke or systemic embolism (SSE) and adjusted for CHA2DS2-VASC and HAS-BLED scores. RESULTS:Of 1739 patients who received an implant (7159 patient-years follow-up; CHA2DS2-VASc=4.0), DRT was seen in 65 patients (3.74%). The rates of SSE with and without DRT were 7.46 and 1.78 per 100 patient-years (adjusted rate ratio, 3.55; 95% confidence interval [CI], 2.18–5.79; P<0.001), and ischemic SSE rates were 6.28 and 1.65 per 100 patient-years (adjusted rate ratio, 3.22; 95% CI, 1.90–5.45, P<0.001). On multivariable modeling analysis, the predictors of DRT were as followshistory of transient ischemic attack or stroke (odds ratio [OR], 2.31; 95% CI, 1.26–4.25; P=0.007), permanent atrial fibrillation (OR, 2.24; 95% CI, 1.19–4.20; P=0.012); vascular disease (OR, 2.06; 95% CI, 1.08–3.91; P=0.028); left atrial appendage diameter (OR, 1.06 per mm increase; 95% CI, 1.01–1.12; P=0.019); left ventricular ejection fraction (OR, 0.96 per 1% increase; 95% CI, 0.94–0.99; P=0.009). DRT and SSE both occurred in 17 of 65 patients (26.2%). Of the 19 SSE events in these patients with DRT, 9 of 19 (47.4%) and 12 of 19 (63.2%) occurred within 1 and 6 months of DRT detection. Conversely, after left atrial appendage closure, most SSEs (123/142, 86.62%) occurred in patients without DRT. CONCLUSIONS:After left atrial appendage closure with Watchman, DRT (≈3.7%) is not frequent but, when present, is associated with a higher rate of stroke and systemic embolism.